Automatic Linking of Wikipedia Pages by Their Semantic Similarity - Ikikat, F. Yesim; Gurhan, Behire; Diri, Banu (IEEE, 2015)
Wikipedia pages associate the key words and phrases from the text with the other Wikipedia pages by linking them together for the purpose of enabling the user to reach the information in an easier way. In this study, by using the Natural Language Processing techniques, the linking system has been tried to be automatized. Initially, the approach has been designed for Turkish Wikipedia, then in the second step, it has been tried for English Wikipedia and the results have been compared, evaluations are promising.
Keywords: wikipedia; automatic hyperlink generation; semantic similarity; zemberek; Computer Science